2013
DOI: 10.1371/journal.pone.0058878
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Relationships among Wood Density, Leaf Structural Traits and Environment in Four Co-Occurring Species of Nothofagus in New Zealand

Abstract: Plant functional traits capture important variation in plant strategy and function. Recent literature has revealed that within-species variation in traits is greater than previously supposed. However, we still have a poor understanding of how intraspecific variation is coordinated among different traits, and how it is driven by environment. We quantified intraspecific variation in wood density and five leaf traits underpinning the leaf economics spectrum (leaf dry matter content, leaf mass per unit area, size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 67 publications
3
27
0
1
Order By: Relevance
“…Additionally, several studies have documented intra‐annual variation in the density of new growth related to climate manipulations (Bouriaud, Leban, Bert, & Deleuze, ; Skomarkova et al, ), and similar relationships are widely used in dendrochronological studies to reconstruct historical climate records (Briffa et al, ). Such experimental evidence, when taken in context with our results and other findings of biogeographical trends of within‐species trends in wood density reported in the literature (Richardson et al, ; Thomas et al, ), indicates that plastic physiological responses are at least in part responsible for driving broad patterns of wood density variation along latitudinal and environmental gradients (Chave et al, ; Muller‐Landau, ; Wiemann & Williamson, ; Williamson & Wiemann, ). This is significant because it suggests that intraspecific variation, whether related to phenotypic plasticity or to regional variation in genotype (Anderegg, ), can contribute to the biogeography of plant traits, rather than broad patterns only arising from species sorting along environmental gradients (Chave et al, ; Swenson & Enquist, ; Swenson et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, several studies have documented intra‐annual variation in the density of new growth related to climate manipulations (Bouriaud, Leban, Bert, & Deleuze, ; Skomarkova et al, ), and similar relationships are widely used in dendrochronological studies to reconstruct historical climate records (Briffa et al, ). Such experimental evidence, when taken in context with our results and other findings of biogeographical trends of within‐species trends in wood density reported in the literature (Richardson et al, ; Thomas et al, ), indicates that plastic physiological responses are at least in part responsible for driving broad patterns of wood density variation along latitudinal and environmental gradients (Chave et al, ; Muller‐Landau, ; Wiemann & Williamson, ; Williamson & Wiemann, ). This is significant because it suggests that intraspecific variation, whether related to phenotypic plasticity or to regional variation in genotype (Anderegg, ), can contribute to the biogeography of plant traits, rather than broad patterns only arising from species sorting along environmental gradients (Chave et al, ; Swenson & Enquist, ; Swenson et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Alternatively, our results might indicate that other accounted for (temperature) and unaccounted for (e.g., competition, soil fertility gradients) factors are stronger drivers of wood density trends at the regional scale. For example, Reich et al (2014) found that the impact of aridity on biomass allocation patterns in trees was limited compared with the direct and indirect effects of temperature gradients, whereas Kunstler et al (2016) (Richardson et al, 2013;Thomas et al, 2004), indicates that plastic physiological responses are at least in part responsible for driving broad patterns of wood density variation along latitudinal and environmental gradients (Chave et al, 2006;Muller-Landau, 2004;Wiemann & Williamson, 2002;Williamson & Wiemann, 2010). This is significant because it suggests that intraspecific variation, whether related to phenotypic plasticity or to regional variation in genotype (Anderegg, 2015), can contribute to the biogeography of plant traits, rather than broad patterns only arising from species sorting along environmental gradients (Chave et al, 2006;Swenson & Enquist, 2007;Swenson et al, 2012).…”
Section: Impact Of Within-and Among-species Climate Trends On Geogrmentioning
confidence: 99%
“…LMA varies considerably across sun leaves of given species; to estimate LMA for the leaves measured for anatomy, we developed empirical equations relating LMA to thickness for sun leaves of given species (Richardson et al . ). For 14–26 sun leaves of each species we averaged turgid leaf thickness (LT) measured at the base, middle and tip between second‐order veins using digital callipers (± 0.01 mm; Fisher Scientific, PA, USA).…”
Section: Methodsmentioning
confidence: 97%
“…The integration of wood traits as an independent variation axis orthogonal to leaf traits has been emphasized in plant ecology (Baraloto, Timothy Paine, et al., ; Chave et al., ; Fortunel, Fine, & Baraloto, ; Richardson et al., ). Wood density is often taken as a key functional wood trait.…”
Section: Introductionmentioning
confidence: 99%